Quality of life in myopia. Issue 9 (1st September 2000) - Rose, Karen; Harper, Robert; Tromans, Cindy; Waterman, Christine; Goldberg, David; Haggerty, Clare; Tullo, Andrew
Abstract : BACKGROUND: The safety and predictability of refractive surgery for all degrees of myopia is now becoming established. It is therefore appropriate to evaluate whether there is a patient driven demand for such treatments and, if so, to establish guidelines for its provision within the National Health Service (NHS). METHODS: A comparative study was designed to assess the effect of degree of myopia on quality of life ("high" (n = 30) –10.00D, worse eye; "moderate" (n = 40) –4.00 to –9.75D, worse eye; "low" (n = 42) <–4.00D, worse eye) compared with a group of patients with keratoconus (n = 30) treated by optical correction. Data collection included binocular logMAR visual acuity, Pelli-Robson low contrast letter sensitivity, questionnaires to assess subjective visual function (VF-14) and effect on quality of life (VQOL), and semi-structured interviews. RESULTS: There were no significant differences in any of the measures between patients with a high degree of myopia and those with keratoconus, or between those with a low and those with a moderate degree of myopia. However, those with a high degree of myopia had highly significantly poorer logMAR, VF-14, and VQOL scores than those with low and moderate myopia (p<0.001). Interview data supported these findings with patients with a high degree of myopia and those with keratoconus reporting that psychological, cosmetic, practical, and financial factors affected their quality of life. CONCLUSION: Compared with low and moderate myopia, patients with a high degree of myopia experience impaired quality of life similar to that of patients with keratoconus. Criteria should therefore be identified to enable those in sufficient need to obtain refractive surgical treatment under the NHS.